Yield and economic impact of less-water consumption techniques in tank irrigated rice (Oryza sativa) and groundnut (Arachis hypogaea) crops - RAMANA, C; REDDY, B RAVINDRANATHA; MUNASWAMY, V; REDDY, B RAVINDRA; PRASHANTHI, A (The Indian Journal of Agricultural Sciences, 2015)
A study was conducted with a view to reduce uncertainty of inflows in supply channels, weed infestation in tank bed and water scarcity during poor monsoon seasons. The less-water consuming technologies and use of improved implements along with matching crop production techniques were demonstrated to improve water productivity. Altogether, the mind-set of tank farmer that more the irrigation, more the yield was changed to controlled irrigation for more production. The new habit of ‘measure and use’ policy even in irrigation water was infused. The water productivity was realized in such a way that the productivity of rice (Oryza sativa L.) in whole command increasedfrom 4.6 kg/ha/mm in 2005 to 7.3 kg/ha/mm in 2009; in groundnut (Arachis hypogaea L.) from 5.6 kg/ha/mm in 2005 to 6.5 kg/ha/mm in 2009. Hence the economic impact of ‘measure and use’ policy was proved its superiority for less-water consumption management in tank irrigation in the cases of rice and groundnut.